Relationship between mother's knowledge and behavior in milk bottle hygiene with diarrhea incidence in infants aged 6-24 months - Lia Mayang Sari Sijabat; Dedi Dedi; Angenia Itoniat Zega; Mulidan Mulidan (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Diarrhea can be defined as a condition when a person defecates more than three times in 24 hours with a more liquid stool consistency than usual. This disease is related to environmental factors and microorganisms such as bacteria, viruses, parasites, and protozoa are the causes, with the possibility of transmission through oral and vertical routes. Purpose: To examine the relationship between the level of knowledge and the incidence of diarrhea in infants aged 6–24 months. Method: This study used an analytical survey method with a cross-sectional approach, involving a total population of 45 respondents. For this study, a total sampling technique was used in sampling. To collect data, this study utilized primary and secondary methods, while data analysis was carried out using the Chi-Square test. A questionnaire was used as an instrument in this study. Results: From the results of the analysis, p = 0.000 (a <0.05) was obtained, which means that there is a relationship between the level of knowledge and behavior of mothers in bottle hygiene with the incidence. Conclusion: It was found that there was a relationship between maternal behavior in maintaining the hygiene of milk bottles and the incidence of diarrhea in babies aged 6-12 months.